LEXICAL UNITS OF LEGAL LANGUAGE - Gulyamova Gulnora Yakubovna (Galaxy International Interdisciplinary Research Journal, 2024)
The adoption of a number of laws related to human rights, in turn, is the reason for the emergence of a number of new legal terms. Since these terms are reflected in the language as legal concepts, words or terms, they must be expressed and formed based on the laws of the national language. The vocabulary of legal language mainly consists of terms. But to express any legal concepts, certain requirements and norms are placed before the terms. This follows from the essence and nature of this term. The process of studying the system of legal terms of the modern Uzbek language shows that the method of lexicalization is extremely active.